(untitled) (Journal of International Studies, 2019)
The discrepancies in Indonesia’s diplomatic approach on the death penalty for its people abroad and other nationalities at home have raised ‘double standard’ concerns. By looking into the factors affecting Indonesia’s diplomatic approach to Australia using the case of Bali Nine, the study explored the rationale of the Indonesian government putting national interest over its human rights commitment despite the increased pressure on its death penalty practice in the debate between human rights and state sovereignty. This study used the interview method with two objectives. First, to investigate the factors influencing Indonesia’s diplomatic approach to the Bali Nine case, and second, to explore the conflict between human rights and state sovereignty by drawing upon the theoretical framework on human rights and foreign policy as proposed by Jack Donnelly. The finding of this paper suggests that human rights interests are subordinated to other national interests in balancing the objectives of Indonesia’s diplomacy on the drug-related death penalty practice.